AB0186 Elevated Indoleamine-2, 3-Dioxygenase (IDO) and Tryptophan Catabolism in Primary SjÖGren's Syndrome Patients, Positive for the Interferon Type I Signature: A Possible Link to Fatigue and Depression. (10th June 2014) - Maria, N.I.; van Helden-Meeuwsen, C.G.; Brkic, Z.; van Daele, P.L.; van Hagen, M.; Gibney, S.M.; Harkin, A.; Drexhage, H.A.; Versnel, M.A.
Abstract : Background: Patients with primary Sjögren's syndrome (pSS) often experience disabling fatigue and a depressed mood as their most severe symptom. These symptoms reduce overall health-related quality of life, having an extensive effect on physical and psychological functioning. We previously identified a subgroup (55-60%) of pSS patients, positive for the IFN type I signature, associated with higher EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) scores, SSA/anti-SSB antibodies, IgG levels, BAFF levels and lower C3 complement levels [Brkic, Maria et al., 2013]. A role for IFN type I in fatigue and depressive symptoms is supported by induction of these symptoms in subjects undergoing IFN type I therapies. Objectives: Previously, indoleamine-2, 3-dioxygenase (IDO) expression was related to IFNα-induced depression. IDO degrades tryptophan, a precursor of the neurotransmitter serotonin (5-hydroxytryptamine) to kynurenine. Aberrant tryptophan catabolism has been associated with mood disturbances. We therefore hypothesized that aberrant IDO expression in IFN type I signature positive patients is related to symptoms of fatigue and depression. Methods: In a cohort of 110 pSS patients and 70 Healthy controls (HC) the IFNscore, a measure for total IFN type I activation, was calculated using expression values of the IFN type I signature genes –IFI44, IFI44L, IFIT3, LY6E, MX1– thereby stratifying patients in IFN-positive (IFNscore>10) and IFN-negative (IFNscore<10) subgroups [Brkic, Maria et al., 2013]. Tryptophan catabolism and IDO-related cytokines (IL1b, IL-4, IL-6, IL10, TNFα & IFNγ) were assessed in serum. Gene-expression of IDO and downstream enzymes (KMO, KYNU & KAT1-4) were measured using RQ-PCR. Furthermore pSS patients where characterized for general fatigue (Multidimensional Fatigue Inventory) and depressive symptoms (CES-D). Results: The described cohort had an IFN type I signature prevalence of 60%. Preliminary results shown in Figure 1 A indicate a highly elevated tryptophan catabolism, confined to IFNpositive-, compared to both IFNnegative-pSS (p>0.01) and HC (p>0.0001). IDO mRNA levels were significantly increased, restricted to IFNpositive CD14+ monocytes (p>0.0001; Figure 1B). IL-6 (p>0.01), IL-10 (p>0.001) and TNFα (p>0.001) were significantly upregulated in IFNpositive pSS compared to HC, whereas IFNnegative patients showed no significant differences. Furthermore, downstream enzymes suggest an inflammatory-driven neurotoxic reduction in serotonin. Data on fatigue-assessment correlations will be presented. Conclusions: Tryptophan catabolism and IDO-related cytokines are highly elevated in pSS, in particular in IFN type I signature positive patients. A disrupted tryptophan catabolism, resulting in reduced serotonin levels, might be the cause of severe fatigue and depression in these patients. Further unraveling this disrupted mechanism, and the possible neurotoxic role of IFN type I, will shed new light on unexplained fatigue in pSS. References: Z. Brkic, N.I. Maria et al. 'Prevalence of interferon type I signature in CD14 monocytes of patients with Sjögren's syndrome and association with disease activity and BAFF gene expression'. Ann Rheum Dis, 2013;72(5). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3725